The Effect of Combined Extracts of Sappan Wood (Caesalpinia sappan L.) and Gotu Kola (Centella asiatica L.) in Improving Diabetic Condition in Rats - Binti Maulina; Wasita, Brian; Febrinasari, Ratih Puspita (Jurnal Gizi dan Pangan, 2022)
This study aimed to determine the efficacy of combination of sappan (secang) wood and gotu kola extracts in reducing insulin resistance and Malondialdehyde (MDA) levels in diabetic rats induced by Streptozotocin (STZ) 65 mg/kg Body Weight (BW) and Nicotinamide (NA) 230 mg/kg BW. Forty-two male Sprague Dawley rats weighing ±200 g were divided into 7 groups: 1) control, 2) glibenclamide 0.45 mg/kg BW, 3) sappan wood extract (CS) 250 mg/kg BW, 4) gotu kola extract (CA) 500 mg/kg BW, 5) 1st combination of extracts of sappan wood and gotu kola (CSCA1) 125 mg/kg BW + 750 mg/kg BW, 6) 2nd combination (CSCA2) with 250 mg/kg BW + 500 mg/kg BW, and 7) 3rd combination (CSCA3) with 375 mg/kg BW + 250 mg/kg BW. The insulin resistance levels were measured using the HOMA-IR index based on fasting blood glucose and insulin. The Thiobarbituric Acid Reactive Substance (TBARs) method was used to measure MDA levels. All measurements were taken before treatment, 14 days after treatment, and 21 days after treatment. The group receiving CSCA3 showed significant reduction in insulin resistance (-3.32±0.05) and MDA levels (-2.04±0.37 nmol/ml) on Day 21 after treatment. The CSCA3 treatment did not show statistically different result compared to glibenclamide treatment (p>0.05). Hence, CSCA3 treatment was considered as the best proportion of sappan wood and gotu kola extracts mixture and the result is comparable to glibenclamide. This study shows that the combination of sappan wood and gotu kola extracts has the potential to be developed as a functional drink for people with diabetes.